Work Stress and Parenting Quality in Working Mothers: Does Emotion Regulation Moderate the Relationship? - Nurul Intan Willyanti; Naomi Soetikno (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examined whether emotion regulation moderates the relationship between work stress and parenting quality among working mothers with children aged 7–11 years. A quantitative, correlational design was employed with purposive sampling. Participants were 304 formally employed working mothers (civil servants and non-shift private employees) from Indonesia; an initial pool of 384 respondents was collected, of whom 80 were excluded due to non-consent, trial entries, or irregular response patterns. Work stress was measured using the HSE Management Standards Indicator Tool (HSE-MS IT), parenting quality using the PAFAS-Parenting subscale, and emotion regulation using the Emotion Regulation Questionnaire (ERQ), assessing cognitive reappraisal and expressive suppression separately. Moderated regression analysis revealed that work stress was negatively and significantly associated with parenting quality (β = −0.284, p < .001, R² = 0.081), indicating that higher work stress is associated with lower parenting quality. However, neither cognitive reappraisal (interaction β = −0.007, p = .897) nor expressive suppression (interaction β = −0.028, p = .618) moderated this relationship. The null moderation effect suggests that general, trait-level emotion regulation may not buffer the impact of work stress on parenting behavior, possibly because stress spills over into parenting through mechanisms other than emotion regulation (e.g., reduced time, fatigue). These findings highlight the importance of direct work stress management interventions for working mothers rather than relying solely on emotion regulation training. Limitations include self-report data, cross-sectional design, and the low reliability of the cognitive reappraisal subscale (α = 0.629). Future research should explore mediating mechanisms and use context-specific measures of parenting-related emotion regulation.